Rancang Bangun Alat Monitoring Pergerakan Objek pada Ruangan Menggunakan Modul RCWL 0516 - Aini, Qurotul; Rahardja, Untung; Madiistriyatno, Harries; Fuad, Azharul (Jurnal Teknik Elektro, 2018)
Nowdays, along with the development of electronics and computers, the crime rate increases rapidly. today almost all systems and security tools are using electronic devices such as computers and microcontrollers. Every electronic device always has weakness, such as camera needs the light to capture images, Passive InfraRed (PIR) sensor only has ability for human body temperature detection, Short Message Service (SMS) which its services depend on prepay credit and cellular operator signal range. Based on the problem, a radio-based doppler radar detection tool was developed using RCWL 0516 module. In this research will be discussed the use of RCWL 0516 sensor as main module to detect the movement of the object by measuring the microwave wave value that displayed on the user gadget by using Blynk application. The digital communication is used and implemented on Arduino Uno microcontroller. The data is sent and will be displayed on the gadget through Blynk application in the form of graph in real time and connect to the internet using ESP8266 as a connection receiver. The results obtained that the RCWL 0516 module has a better accuracy level in detecting movement than other motion detection sensors such as PIR sensors and ultrasonic sensors.